Comprehensive analysis and development of deep learning models for Bengali character’s spectrogram image classification in child speech: introduction of spectro SETNet - Ahmed, Syed Istiaque; Hossain, Md. Jubayer; Hoque, Kayes Mohammad Bin; Tusher, Mahmadur Rahman; Islam, Sajedur (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.